2006
DOI: 10.1097/01.rli.0000244341.16372.08
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Determination of Hepatic Stiffness Using Steady-State Free Precession Magnetic Resonance Elastography

Abstract: bSSFP combined with fractional MRE enables rapid measurement of liver stiffness in vivo. The used actuation principle supports a 2-dimensional analysis of the strain wave field captured by axial wave images. The measured data indicate individual variations of hepatic stiffness in healthy volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 32 publications
1
93
0
2
Order By: Relevance
“…shear waves) are waves with motion perpendicular to their propagating direction. The generated shear waves observed here had bilateral directivities, as has been observed by other researchers (25,(28)(29)(30)(31), and did not propagate simply along two parallel straight lines. Instead, they were prone to deviate from the center axis and formed a biased diffraction field.…”
Section: Analysis Of the Shear Wave Fieldsupporting
confidence: 85%
See 1 more Smart Citation
“…shear waves) are waves with motion perpendicular to their propagating direction. The generated shear waves observed here had bilateral directivities, as has been observed by other researchers (25,(28)(29)(30)(31), and did not propagate simply along two parallel straight lines. Instead, they were prone to deviate from the center axis and formed a biased diffraction field.…”
Section: Analysis Of the Shear Wave Fieldsupporting
confidence: 85%
“…The mean displacement amplitude and the mean shear stiffness (using the Direct Inversion algorithm (25,(28)(29)(30)(31)) were calculated in all shear wave images by using a standardized region of interest (square ROI, 20×20 pixels) positioned 15-mm below the driving surface.…”
Section: Dependence Of Wave Amplitude and Shear Stiffness On Imaging mentioning
confidence: 99%
“…These include 1) a freely oriented field of view, 2) no need for acoustical window in contrast to transient elastography, 3) compatibility with many other receive coils such as multi-channel phased array torso coil, 4) operator independence, 5) insensitivity to body habitus, 6) the ability to obtain a conventional MR examination at the same time (27)(28)(29), and 7) potential to assess the entire liver with an appropriate rapid multislice method, as echo-planar MR Elastography (42). Thus, this technique provides an overall estimate rather than a narrow sliver obtained with ultrasound transient elastography or liver biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…MR Elastography can be readily implemented on standard MR imaging systems with little additional hardware (21). To date, MR Elastography has been applied to quantitatively assess the viscoelastic properties of many human tissues in vivo, including breast, brain, muscle, and liver (22)(23)(24)(25)(26)(27)(28)(29). Preliminary studies in human subjects have confirmed the feasibility and promise of this technique for the quantitative assessment of hepatic fibrosis (27,28).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the accuracy of MRE potentially outperforms that of other modalities with anisotropic motion estimation. However, MRE still suffers from uncertainty regions in elastograms, which have to be masked in order to avoid biased stiffness estimates [16,17]. Such artifacts are mainly due to the strong impact of boundaries and tissue interfaces on the appearance of wave fields including non-evanescent waves, wave nodes, and amplitude modulations deviating from ideal wave models implied by the majority of inversion routines.…”
mentioning
confidence: 99%